2021
DOI: 10.1111/jgh.15509
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid enhancement of lymphocyte migration through direct interaction with the intestinal vascular endothelium

Abstract: Background and Aim The small intestine plays a central role in gut immunity, and enhanced lymphocyte migration is involved in the pathophysiology of various enteropathy. Bile acid (BA) is closely related to lipid metabolism and gut microbiota and essential for gut homeostasis. However, the effects of BA on gut immunity have not been studied in detail, especially on the small intestine and lymphocyte migration. Therefore, we aimed to investigate the effect of BA on small intestinal lymphocyte microcirculation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Interestingly, the levels of the bile acid, deoxycholic acid was also significantly reduced by TNF-α treatment and was further suppressed when co-treated with 60 °C OPWE ( Table 2 ). To date, the role of bile acids on endothelial cells remains controversial; while some studies have reported the pro-inflammatory effects of bile acids [ 49 , 50 ], others have demonstrated their vasoprotective effects [ 51 , 52 ]. Specifically, an earlier study reported that bile acids had enhanced adhesion molecule expression in endothelial cells [ 50 ] through oxidative stress and activation of NF-kappaB and p38 signalling pathway [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the levels of the bile acid, deoxycholic acid was also significantly reduced by TNF-α treatment and was further suppressed when co-treated with 60 °C OPWE ( Table 2 ). To date, the role of bile acids on endothelial cells remains controversial; while some studies have reported the pro-inflammatory effects of bile acids [ 49 , 50 ], others have demonstrated their vasoprotective effects [ 51 , 52 ]. Specifically, an earlier study reported that bile acids had enhanced adhesion molecule expression in endothelial cells [ 50 ] through oxidative stress and activation of NF-kappaB and p38 signalling pathway [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, the role of bile acids on endothelial cells remains controversial; while some studies have reported the pro-inflammatory effects of bile acids [ 49 , 50 ], others have demonstrated their vasoprotective effects [ 51 , 52 ]. Specifically, an earlier study reported that bile acids had enhanced adhesion molecule expression in endothelial cells [ 50 ] through oxidative stress and activation of NF-kappaB and p38 signalling pathway [ 49 ]. This suggested that elevated levels of bile acids may cause endothelium dysfunction and contribute to the initiation of early events of vascular inflammation [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deoxycholic acid (DCA) enhanced ileal lymphocyte migration in part by up-regulating adhesion molecule expression through sphingosine-1-phosphate receptor 2 (S1PR2), and S1PR2 antagonist alleviated indomethacin-induced and DCA-exaggerated small bowel injury ( Shibuya et al, 2021 ). Bile acid receptor S1PR2 may play a proinflammatory role in the intestine.…”
Section: Factors Involved In the Pathogenesis Of The Nsaid-associated...mentioning
confidence: 99%
“…The properties of DCA rely on its capacity to activate several carcinogenesis-related cell signaling pathways, including protein kinase C (PLC) [ 250 ], ERK1/2 via the epidermal growth factor receptor [ 255 , 256 , 257 ], β-catenin [ 258 ], JNK1/2 [ 259 ] and activation of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome [ 260 ]. DCA also induces and exacerbates intestinal inflammation as well as associated dysbiosis [ 261 , 262 , 263 ]. Increased amounts of DCA in the bile of a subset of cholesterol gallstone patients correlate with the abundance of CA 7α-dehydroxylating fecal bacteria.…”
Section: Basmentioning
confidence: 99%